Alain Renaut. Political Philosophy: Applied and Global - Karounia, Catherine (Conatus - Journal of Philosophy, 2017)
The following conversation with Alain Renaut, emeritus Professor of Political Philosophy and Ethics at the University of Paris-Sorbonne (Paris IV), and director of the International Centre for Applied Political Philosophy (CIPPA), was conducted following the CONATUS magazine’s request, namely to discuss his current research interests. The interview took place on 15/04/2016, at the Maison de la Recherche of the same University and on the occasion of his latest monograph’s publication, entitled L’injustifiable et l’extrême: manifeste pour une philosophie appliquée. The reader will ascertain the role that Political Philosophy is due to play regarding human reality, as Renaut’s interest is focused on issues which require practical solutions. In this context, reference is made to extreme natural phenomena, such as the 2010 earthquake in Haiti that caused a great many victims. Also, an important part of the discussion is devoted to the refugee and immigration questions. Extreme climate change, and the risks posed by these new facts in globalisation conditions, are also examined.